Different Ferromanganese Concretion Morphologies Host Distinct Microbial Communities and Metal Accumulation Patterns in the Baltic Sea - Majamäki, Renata; Wasiljeff, Joonas; Purkamo, Lotta; Hultman, Jenni; Kohl, Lukas; Asmala, Eero; Yli‐Hemminki, Pirjo; Jørgensen, Kirsten S.; Muurinen, Johanna; Virtasalo, Joonas J. (Wiley-Blackwell, 2026)
Ferromanganese (Fe-Mn) concretions are porous accumulations of iron and manganese (hydr)oxides. While recent studies suggest that microbes contribute to metal accumulation in Baltic Sea concretions, the detailed composition of microbial communities and their impact on metal enrichment across different concretion morphotypes remain unexplored. We investigated how microbes influence the accumulation and release of trace metals and rare-earth elements in Fe-Mn concretions from the Gulf of Finland through 15-week microcosm incubation experiments with biotic and abiotic treatments, focusing on three main concretion morphotypes: crust, discoidal, and spheroidal. Elemental analysis showed that microbes enhanced metal incorporation in discoidal and spheroidal morphotypes. Characterisation of microbial composition revealed that all three morphologies host distinct communities. Discoidal and spheroidal morphotypes had a higher relative abundance of Gammaproteobacteria and sulfate-reducing bacteria, and a lower abundance of Entotheonellaeota, compared to crusts. In all morphotypes, the bacterial phylum Pseudomonadota dominated, with several genera of Fe- and Mn-oxidisers and reducers. Fe-Mn concretions also host communities involved in methane oxidation and nitrogen cycling, consistent with decreased methane and increased nitrous oxide, nitrite, and nitrate concentrations in the microcosms. Our findings underscore that distinct microbial communities are associated with different concretion morphotypes, potentially influencing nutrient and metal cycling on the seafloor.
Keywords: Baltic Sea; brackish water; ferromanganese; geomicrobiology; microbial ecology; nodules; rare-earth elements; trace elements